Eshatološki mir v Vergilijevi četrti eklogi in Hölderlinovi "Slovesnosti miru" - Snoj, Vid (Primerjalna književnost, 2015)
This article compares two great poems of European peace literature. It presents the historical circumstances of their creation, but refrains from attempting to historically identify their main characters, the (divine) child (puer) and the Prince of the Feast (Fürst des Festes), and focuses on their eschatological poiesis - the versifying of what comes last at the end of time, the crown of which is peace.
Keywords: Vergilius Maro, Publius, 70-19 pr.n.š.; Hölderlin, Friedrich, 1770-1843; književnost in religija; latinska poezija; nemška poezija; eshatologija; mir